Science , Technology in Colonial India: A growth of Scientific Ideas and Practices of late 18th and early 19th Centuries India - Doley, Debobrat (International Journal of Advanced Science and Technology, 2019)
It would be erroneous to consider India as having one scientific tradition. Over the millennia, India became heir to a good sort of different oral and textual traditions, drawing upon exogenous contacts as well as indigenous roots. This plurality makes it difficult not only to characterise Indian science as a whole but also to determine the precise nature of its interaction with the forms of science and technology procced from the West by the late 18th and early 19th centuries. Even within what is often thought of as the ‘Hindu’ tradition, there were several strands of scientific ideas and practices, including a tradition of empirical, observational science (particularly developed in astronomy and medicine) that functioned alongside, and often in tandem with, various cosmological and astrological beliefs. Orientalist  of the late 18th and early 19th centuries represented India as having had an ancient civilisation equalling in some respects excelling or anticipating, those of classical Greece and Rome. In this paper atempts to analyse the scientific, technological and medical developments of the period from the 17th century to the 20th centuries of India.